Performance of Zambian Commercial Banks in the Post-Liberalisation Period: Evidence on Cost Efficiency, Competition and Market Power - Simpasa, Anthony Musonda (School of Economics, 2014)
This study investigates three aspects important of performance for Zambia commercial banks. Specifically, the thesis addresses the aspect of cost efficiency and the factors that affect inefficiency performance. The study also empirically answers the policy question regarding the banks' exercise of market power and the low degree of competition. Using a richly assembled panel data set obtained from the Bank of Zambia on individual banks from 1998 to 2006, the thesis utilises theoretically sound methodologies in addressing these research questions. The results from the analysis reveal the following. Firstly, using stochastic frontier estimation approach, cost inefficiency was estimated to be 8 percent. This means that mismanagement of resources was an impediment to the efficiency performance. Nonetheless, we observed a reduction in cost inefficiency over time, with domestic private banks displaying remarkable improvement. A combination of bank-specific and exogenous factors deterred banks from attaining optimal cost efficiency. Notably, impaired loans, asset concentration and macroeconomic instability undermined the banks' ability to operate optimally. Regulatory factors did not exacerbate cost inefficiency. Secondly, Zambian banks operated in an oligopolistic set-up. Based on a methodology anchored in the New Empirical Industrial Organisation literature, the results of a competitive test showed that banks earned their revenue under conditions of monopolistic competition. This finding was buttressed by the estimated time varying Lerner Index, a measure of market power. The index showed that commercial banks set their prices above marginal cost by more than 50 percent. However, the degree of market power narrowed towards the end of the sample period. Market concentration, efficiency performance, diversity in revenue sources and regulatory intensity accounted for much of the banks' exercise of market power. On the other hand, the high proportion of interbank deposits, credit risk exposure and inflation dampened the banks' exercise of market power. To our knowledge, this study is the first of its kind in Zambia. Therefore, the results of the thesis have important policy implications. More significantly, since there is room for deepening the degree of competition and furthering efficiency gains, regulatory authorities should strengthen measures aimed at ameliorating risk problems in the banking industry in a bid to lower the banks' exercise of market power. The authorities should also accelerate should also accelerate efforts of reducing recourse to Treasury bills as a deficit financing tool in order to negate the banks' appetite for securities as a source of revenue. This can be done by placing more emphasis on the legal and institutional framework for resolving problem credit situations. This will intensify competition and propagate efficiency gains in the banking market. The authorities should also expeditiously tackle instability in the macroeconomic environment, particularly the high rate of inflation which hampered the banks' revenue performance and exacerbated the exercise of market power